(untitled) (Journal of history, 2021)
The article describes the history of the study of the Stone Age of East Kazakhstan, since the first half of the twentieth century and before the independence of our country, this region has always attracted special attention of scientists. To date, it is known that since the mid-20th century and until the early 90s, more than 10 monuments of Paleolithic time have been discovered, such as the Cave, Novo-Nikolskoye, Kanai, Svinchatka, Ust-Narym, Bolyshenarymskoye and Malonarymskoye, Shulbinka, Kozybai, etc. As a result of the work carried out, the first monuments of the Paleolithic period of East Kazakhstan, recog- nized by a wide range of specialists, were discovered for decades, exploration works were carried out, as a result of which a good collection of stone products dated to the Paleolithic was collected, and the first measures were taken to interpret these finds. Including All the described Paleolithic sites of Eastern Kazakhstan, as well as the identified stone artifacts from the sites, show the consistent development of Paleolithic culture in the Irtysh River valley, starting from the Mustier era and up to the end of the Pleis- tocene and the beginning of the Holocene. It is quite logical that the stone industry of the above-listed monuments reveals a great similarity with the monuments that were discovered in modern times and requires a new rethinking. Key words: East Kazakhstan, Stone Age, Paleolithic, site, stratigraphy, horizon, artifacts, fauna, cul- tural layer, nucleus, retouching, pit, levallois.